THE INFLUENCE OF IMPLEMENTING THE MAKE A MATCH TYPE COOPERATIVE LEARNING MODEL ON THE LEARNING MOTIVATION OF CLASS XII IPS STUDENTS IN THE SUBJECT OF ECONOMICS AT SMA NEGERI 8 BULUKUMBA - Ihzatul Adrifa Azis; Hajerah Hasyim; Fajriani Azis; Nuraisyiah .; Sahade . (JURNAL EDUSCIENCE, 2023)
This research aims to analyze the effect of implementing the make a match type cooperative learning model on the learning motivation of class XII IPS students in economics subjects at SMA Negeri 8 Bulukumba. The variables of this research are the make a match type cooperative learning model as the independent variable (X) and learning motivation as the dependent variable (Y). The population of this study was all students of class XII IPS, totaling 76 students, while the sample in this study was students of class The data collection techniques used are documentation and questionnaires. The data analysis techniques used are descriptive statistical analysis, instrument testing and hypothesis testing using SPSS 29 for Windows. The results of this research show that: (1) Based on the results of simple linear regression analysis, the value of r2 = 58.6% is obtained, which means that the make a match model has an influence on student learning motivation of 58.6 percent while the remaining 41.4 percent is influenced by factors. other. (3) From the Pearson product moment correlation analysis, the Pearson correlation value is 0.766 and the positive value is in the interval 0.61-0.80 which is in the strong category, which means there is a strong relationship between the make a match model and student learning motivation. (4) From the results of the t-test analysis, the significance value is 0.001 < 0.05, which means that the make a match model variable has a positive and significant effect on the learning motivation of class XII IPS students in the Economics subject at SMA Negeri 8 Bulukumba, thus the hypothesis " accepted"